Challenges with Implementing the Centers for Disease Control and Prevention Opioid Guideline: A Consensus Panel Report. Issue 4 (25th January 2019) - Kroenke, Kurt; Alford, Daniel P; Argoff, Charles; Canlas, Bernard; Covington, Edward; Frank, Joseph W; Haake, Karl J; Hanling, Steven; Hooten, W Michael; Kertesz, Stefan G; Kravitz, Richard L; Krebs, Erin E; et al.
Abstract: Background: A national crisis of opioid-related morbidity, mortality, and misuse has led to initiatives to address the appropriate role of opioids to treat pain. Deployment of a guideline from the Centers for Disease Control and Prevention to reduce the risks of opioid therapy has raised substantial clinical and public policy challenges. The agency anticipated implementation challenges and committed to reevaluating the guideline for intended and unintended effects on clinician and patient outcomes. Observations: A multidisciplinary expert panel met to review the influence of the core recommendations of the guideline on pain management practices, principally regarding the estimated 5 to 8 million Americans with chronic pain currently on opioids. The panel identified implementation challenges, including application of dosage ceilings and prescription duration guidance, failure to appreciate the importance of patient involvement in decisions to taper or discontinue opioids, barriers to diagnosis and treatment of opioid use disorder, and impeded access to recommended comprehensive, multimodal pain care. Furthermore, policy-making and regulatory bodies may misapply guideline recommendations without flexibility and, sometimes, without full awareness of what the guideline contains. Conclusions and Relevance: The panel largely supported the guideline, endorsing its focal points of safety and comprehensive assessment and monitoring. To mitigate clinical and policy challenges identified with implementing the guideline, the panel discussed areas where viewpoints diverged and arrived at consensus proposals. The target audience includes the leaders and institutions that create policy and influence guideline implementation to include regulatory agencies, legislators, public and private payers, and health care systems.